The role of ants in land reclamation seeding operations - Majer, Jonathan (1990)
The mining industry contributes a sizeable portion of the Australian economy. Extracted materials include coal, uranium, iron ore, bauxite and mineral sands. Most of these are extracted by open-cut mining operations. The legislative arrangements between the various mining companies and the respective State or Federal Government agencies generally require that the disturbed land be rehabilitated to an appropriate post-mining land use. In view of the fact that mining is often carried out in areas of native vegetation, restoration of the original vegetation is frequently a common goal of the rehabilitation program.